Fostering Social-Emotional Growth through Cooperative Learning in Early Childhood Education - Siswantini, Yuli; Kuswandi, Dedi; Samawi, Ahmad (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study examines the enhancement of children's social-emotional development through the application of cooperative learning strategies in early childhood education. Adopting a qualitative case study approach, data were collected through interviews, observations, and documentation. The data were analyzed systematically using techniques of data display, reduction, and conclusion drawing. Findings reveal that social-emotional growth in early childhood can be significantly improved through structured cooperative learning activities that include clear role division within groups, the use of positive feedback and rewards, and strategies aimed at fostering self-confidence and independence. The implementation of these practices not only enhances children's social interaction skills but also supports emotional regulation and resilience. The study highlights the critical role of collaborative learning in shaping key aspects of social-emotional development, offering practical implications for educators in early childhood settings. Structured group activities, meaningful participation, and positive reinforcement are shown to be effective tools for nurturing interpersonal competence and autonomy in young learners, laying a strong foundation for future developmental outcomes.